Occurrence of Staphylococcus spp. in the wastewaters from Iran: Diversity, antimicrobial resistance, and virulence potential. (3rd February 2023) - Ranjbar Omid, Mahsa; Jamali, Houshang; Kafilzadeh, Farshid; Borjian, Amir; Arzanlou, Mohsen
Abstract: The prevalence, antibiotic resistance, and virulence characteristics of Staphylococci from hospitals, livestock, municipals, and poultry wastewaters were investigated in Ardabil, Iran. From 155 staphylococcal isolates, 44.5% were coagulase-positive Staphylococcus (CoPS) and 55.5% were coagulase-negative Staphylococcus (CoNS) spp. Both CoPS and CoNS species were mainly found in hospital and poultry wastewater samples. The most prominent CoPS and CoNS species were Staphylococcus aureus at 80% and Staphylococcus xylosus at 37%. Methicillin resistance was found in 2% of S. aureus isolates. Overall, 49.2% of CoPS and 47.6% of CoNS isolates exhibited multidrug resistance phenotypes. CoPS isolates were the most resistant to penicillin (89%) and erythromycin (62%) and CoNS isolates exhibited the highest resistance to erythromycin (55%) and tetracycline (49%). Inducible clindamycin resistance was detected in 11% of S. aureus isolates. The ermC and aac genes were detected as the most common macrolide–lincosamide–streptogramin B and aminoglycoside-resistance encoding genes in 82.5 and 22.5% of S. aureus isolates, respectively. Most of the S. aureus isolates were positive for multiple virulence factors. The methicillin-resistant S. aureus isolates belonged to SCC mec type V. A new spa type t19215 was also identified. The occurrence of multidrug-resistant S. aureus with diverse genetic resistance and virulence background in wastewater is of great health concern. HIGHLIGHTS: Ten coagulase-negative and four coagulase-positive Staphylococcus spp. were identified in wastewaters in Iran. 50% of both coagulase-negative and coagulase-positive Staphylococcus spp. isolates were multidrug-resistant. Occurrence of methicillin-resistant S. aureus was rare in wastewater samples in Iran. S. aureus isolates with high virulence potentials were common. A new spa type t19215 was identified in S. aureus isolates. Graphical Abstract